Quantification of fairness perception by including other-regarding concerns using a relativistic fairness-equity model - Tam, Nicoladie (Advances in Social Sciences Research Journal, 2014)
Using a relativistic fairness-equity model, this study quantifies the fairness perception by a stimulus-response function. Fairness often requires the comparison between two parties in social interactions. The relativistic model of fairness assessment takes into the account of the relativity in the comparison, depending on whether the comparison is based on a self-centered or an other-centered frame of reference. Using the Ultimatum Game (UG) experimental paradigm, fairness perception is quantified by the fairness stimulus-response function, where the y-intercept represents the baseline fairness and the slope represents the fairness sensitivity. UG is a classical behavioral economic task where a sum of money is split between two parties, and the human subjects are asked to accept or reject the share depending on whether they consider the offer as fair or not. The results show that fairness perception is proportional to the offer-ratio between the proposer and the responder using the self-centered frame of reference, with one exception. The exception is that, at absolute equity (equal share between the two parties), the subjects reported the offer as the fairest, even fairer than the most hyper-equitable offers. This suggests that the subjects can switch the frame of reference by not only using a self-centered frame of reference, but also include an other-centered frame of reference in the assessment of fairness. That is, by switching from a local (subjective) frame of reference to a global (objective) frame of reference, the optimization for fairness for both parties can be achieved, resolving the relativistic dilemma that fairness for one person is unfairness for another person. This shows that the relativistic model can describe how fairness perception can be biased relative to the two parties, using a self-centered and an other-centered frame of reference.